PROSPEKTIF JUMLAH PENGUNJUNG DAN USAHA PENGEMBANGAN OBJEK WISATA SARIBU RUMAH GADAANG DI KABUPATEN SOLOK SELATAN - Novita Fatmi Ningsih; Syafri Anwar (JURNAL BUANA, 2021)
This study aims to determine: 1) Prospects of Saribu Tourism of Rumah Gadang in Solok Selatan Regency, 2) Efforts to increase the number of visitors to Saribu Tourism Object of Rumah Gadang Solok Selatan Regency. This type of research uses the mix methode with a sequential explanatory strategy. The population of this study were all visitors of the Saribu Tourism Object. The sample of respondents consisted of 33 people. 23 tourists and 10 tour managers. Data collection techniques include observasion, questionnaire interviews and documentation. Data analysis techniques using SWOT analysis technique. The result showed that the prospec of attractions of the Saribu Gadang house was seen from the knowledge of tourism 54% knew from friend or family. For 50% accessibilty, it is quite good, transportations 47% using a motorcycle. Facilities and infrastuctures supporting tourist objects are deemed insufficient. Cultural attractions that are not continiu. In an effort to increase the number of visitors in the future by completing the lack of infrastrukur, increasing promotions and publications, repairing samaged roads, and attracting more attractions